2021
DOI: 10.7202/1079790ar
|View full text |Cite
|
Sign up to set email alerts
|

Performance Preparation, Anxiety, and the Teacher. Experiences of Adolescent Pianists

Abstract: The purpose of this study was to examine the experiences of adolescent pianists in their private lessons and solo performances in regard to concert preparation and music performance anxiety (mpa). A particular focus was placed on the student-teacher relationship and the potential role of teachers in students’ preparation, experience, and anxiety in performance situations. 62 piano students completed questionnaires pertaining to their private lessons, teacher, and performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
0
13
1
Order By: Relevance
“…Certainly, age has been linked with performance anxiety in previous studies, although the results have been inconsistent (Salmon & et. al, 1989; Steptoe & Fiddler, 1987; van Kemenade et al, 1995; Wolfe, 1989) and previous studies have linked adolescence to a heighted experience of anxiety (Ryan, 2005; Ryan et al, 2021). It may be that the early stage of adolescence is also reflected in children’s feelings about performance.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Certainly, age has been linked with performance anxiety in previous studies, although the results have been inconsistent (Salmon & et. al, 1989; Steptoe & Fiddler, 1987; van Kemenade et al, 1995; Wolfe, 1989) and previous studies have linked adolescence to a heighted experience of anxiety (Ryan, 2005; Ryan et al, 2021). It may be that the early stage of adolescence is also reflected in children’s feelings about performance.…”
Section: Discussionmentioning
confidence: 94%
“…Teachers may play a role in perpetuating some of the perfectionism and anxiety surrounding the performance experience. In studies by Ryan (2004) and Ryan et al (2021), it was evident that most young musicians are encouraged to perform but are not really taught how to do it. Practice performances are rare and most studio work focuses on perfecting the repertoire selections, with very limited instruction as to how to transfer playing skills into performing skills.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Papageorgi, 2006; J. Papageorgi, 2020; Patston & Osborne, 2016; Rae & McCambridge, 2004; Rothlisberger, 1992; Ryan, 1998, 1999, 2000, 2004, 2006; Ryan & Andrews, 2009, 2021; Ryan et al, 2021; Sarbescu & Dorgo, 2014). Indeed, researchers of one study suggested that it presents even earlier in preschool-age children (Boucher & Ryan, 2011) and may have both innate and developed components.…”
Section: Mpa and Perfectionismmentioning
confidence: 99%